2015
DOI: 10.3899/jrheum.141647
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Diastolic Heart Failure in Patients with Rheumatoid Arthritis Correlates with Active Disease, but Not with Treatment Type

Abstract: Recognition of all diastolic HF in RA requires a complex diagnostic approach. Active rather than inactive RA places patients at a higher risk for HF, whereas influence of RA treatment on HF risk needs to be elucidated in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
26

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 54 publications
(76 reference statements)
2
31
1
26
Order By: Relevance
“…There are conflicting results from previous studies that investigated connections between diastolic dysfunction and RA. While some trials concluded that there are correlations between left ventricular diastolic dysfunction and RA, other trials reported no significant correlations regarding the two conditions . The present RA population exhibited a median E/A ratio below one while the median e’ was within the normal range, suggesting a grade 1 diastolic dysfunction (impaired relaxation).…”
Section: Discussioncontrasting
confidence: 56%
“…There are conflicting results from previous studies that investigated connections between diastolic dysfunction and RA. While some trials concluded that there are correlations between left ventricular diastolic dysfunction and RA, other trials reported no significant correlations regarding the two conditions . The present RA population exhibited a median E/A ratio below one while the median e’ was within the normal range, suggesting a grade 1 diastolic dysfunction (impaired relaxation).…”
Section: Discussioncontrasting
confidence: 56%
“…Additionally, RA-related parameters (patient's disability, pain, severity of RA, RF positivity) were associated with prevalent HF [16,45]. Disease activity is also considered to be an independent risk factor of HF as well as systemic inflammation (ESR, CRP) or duration of RA [46,47]. Besides several RA characteristics, the use of GC was also associated with HF after adjustment for CV risk factors and CHD.…”
Section: Rheumatoid Arthritis and Heart Failurementioning
confidence: 95%
“…In the study of Bhatia et al, the prevalence of systolic dysfunction was three times more common as compared to general population [57]. In some studies, HF in RA has been associated with concentric LV hypertrophy and reduced longitudinal strain [46,47].…”
Section: Rheumatoid Arthritis and Heart Failurementioning
confidence: 98%
“…Of note, RA, independently of treatment strategies, is associated with higher risk of heart failure, higher disease activity and disease duration of more than 10 years being independent risk factors [76]. In a subgroup analysis Solomon et al showed that the heart failure risk in the elderly RA patients (>65 y.o.)…”
Section: 12tolerability and Safetymentioning
confidence: 99%